Treatment and management of 1,5 cm diameter appendiceal neuroendocrine tumors: a gray zone - Montali, Filippo; D'Agostino, Filippo; Annicchiarico, Alfredo; Rollo, Alessio; Virgilio, Edoardo; Costi, Renato (Acta Biomedica Atenei Parmensis, 2024)
Appendiceal neuroendocrine tumours are rare and often diagnosed as incidentalomas after an appendectomy for acute appendicitis. Appendiceal tumours can cause appendiceal torsion, eventually resulting in acute appendicitis. In the international guidelines (NANTS and ENETS), tumour size is the main prognostic factor and is associated with os and lymph node relapse (LNM). Right hemicolectomy for tumours >2cm in diameter and simple appendicectomy for those <2cm, and linfadenectomy are generally recommended. Management of tumors between 1 and 2 cm, is still a matter of debate. With this case report we try to deepen this debate, about which clinical and surgical choice to undertake.